Experiences of health sciences students residing on campus during university recess: a photovoice study - Kekana, Palesa Mildred (University of the Free State, 2023)
This study addressed the lack of empirical research on the experiences of South African health sciences students residing on campus during university recess. The health professional governing bodies in South Africa require students to gain clinical competence through work-integrated learning, which is often undertaken during university recess. Yet, literature on this specific topic could not be retrieved. Studies on clinical learning in the health sciences environment focus solely on the clinical workplace, without considering students residing in campus residences during recess. The unknown struggles and potential challenges faced by health sciences students during recess could raise significant issues that higher education institutions in South Africa should consider. To address this research gap, participatory research utilising the photovoice method was employed to answer the research question: what are the experiences of health sciences students residing on campus during recess at a specific university? Four health sciences students were recruited through purposive sampling to participate in a series of workshops. They were provided with cameras to document their experiences on campus during university recess. Discussions and an exhibition of the photographs were conducted, resulting in the identification of 13 themes that were clustered into four, namely, sharing personal space, support services and structures, security, and character building and personal development. These clustered themes flagged that the co-researchers experienced a loss of sense of belonging, linked to inadequate support during university recess. Moreover, the study demonstrates the feasibility of implementing participatory research under challenging conditions, such as COVID-19 restrictions. The participatory method empowered co-researchers to advocate for themselves and others, thereby shedding light on issues that matter for institutional transformation. It would be advantageous to expand the research with more participants, across disciplines, and over longer periods of recess to inform policies and guidelines relating to recess periods.
Dissertation (M.Sc.(Nursing))--University of the Free State, 2023
Keywords: Health sciences students; Student experience; Campus residence; University recess; Photovoice